Ambient Assisted Living. ICT-based Solutions in Real Life Situations 7th International Work-Conference, IWAAL 2015, Puerto Varas, Chile, December 1-4, 2015, Proceedings - Cleland, Ian; Guerrero, Luis; Bravo, José (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of the 7th International Work-Conference on Ambient Assisted Living, IWAAL 2015, held in Puerto Varas, Chile, in December 2015. The 20 full papers presented with 7 short papers were carefully reviewed and selected from 31 submissions. The focus of the papers is on following topics: ambient assisted living for tele-care and tele-rehabilitation; ambient assisted living environments; behaviour analysis and activity recognition; sensing for health and wellbeing; human interaction and perspectives in ambient assisted living solutions.